Structure, mechanical and thermal behaviour of mixtures of polyester resin and dental ceramic waste (2016)
The tensile strength and bending strength, structure and thermal behaviour of mixtures of polyester resin (P-2000) and powders (ASTM sieve 200, <75μm) of dental ceramic wastes (dentals impressions, alginate and gypsum) was reported. The samples consisted of mixtures with percentage weights of 50-50%, 60-40%, 70-30%, 80-20%, 90-10%, where the resin was the majority phase, the Mekc (4% wt) was used as catalyst. The structure was studied using SEM and XRD, the thermal behaviour using DSC, TGA and DMA, while the mechanical strength was tested using standards ASTM D790 and D638. Irregular morphology and presence of small agglomerations was observed, with particle sizes between 29.63 and 38.67μm, the presence of different phases of calcium sulphate was found, and that to the increasing the concentration of the powder, the materials becomes more crystalline, increasing its density. An average service temperature of 69.15±4.60°C was found. Vickers hardness values are reported in ranges from 18.65 to 27.96. Considering the elastic modules was established that the materials become more rigid by having more powder concentration.